IMPLEMENTASI KOMPETENSI PEDAGOGIK GURU MELALUI PROBLEM BASED LEARNING PADA KURIKULUM MERDEKA - Ningtiyas, Rahma Aulia; Bahrodin, Ariga (PGMI UNHASY, 2025)
One of the skills that teachers must have in the teaching process is pedagogical competence, which is very important in the implementation of the Merdeka Curriculum. PBL (Problem Based Learning) is an effective teaching model to improve students' critical thinking and problem-solving skills. This study uses a qualitative approach using the case study method. Data were collected through observation, interviews, and documentation. Primary data sources are the head of the madrasah, teachers, and students, as well as secondary data from other students. Data analysis was carried out by data reduction, data presentation, and drawing conclusions, with triangulation of sources and techniques to check the validity of the data. The results of the study showed that (1) Teachers improve educational foundations, recognize character differences, develop curriculum, design learning, educational and dialogic learning, conduct evaluations, develop student potential (2) Teachers provide problems from real life, formulate problems clearly, according to level, breadth and purpose and are beneficial for students. (3) The inhibiting factors are time constraints, lack of facilities, diverse student abilities and limited teacher human resources. The supporting factors are student skills and enthusiasm and real life problems.